Adaptive spatio-temporal CFAR and multiple-hypothesis tracking system - Hughes, Evan J.; Lewis, Michael B. (Cranfield University, 2009)
This paper describes a self organising spatio-temporal radar CFAR system that uses multiple intelligent software agents to detect and adapt the processing to features in the environment. By combining both temporal and spatial data gathering sufficient samples can be collected to allow both the first and second order moments of the clutter distribution to be approximated for each cell. By gathering higher order statistics to a useful accuracy, more stable thresholds may be produced.
3rd EMRS DTC Technical Conference – Edinburgh 2006